Republic of Latvia : Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2001)
Latvia's economy has emerged from the recession triggered by the Russian crisis. Executive Directors commended the strong economic growth and low inflation. They appreciated the open and liberal trade system and the soundness of the banking system. They emphasized the need to maintain fiscal and monetary policies, and accelerate structural reforms. They urged the authorities to implement reforms to improve private sector development, increase foreign direct investment, enhance governance, and also to privatize state-owned enterprises, and approved a Stand-By Arrangement for the country.